Insights into agroecological farming practice implementation by conservation-minded farmers in North America - Silva, Erin M.; Wezel, Alexander; Stafford, Caley; Brives, Jeanne; Bosseler, Nathan; Cecchinato, Nicole; Cossement, Camille; Ranaldo, Marzia; Broome, Megan (Frontiers in Sustainable Food Systems, 2023)
The transformation of our food system towards a more resilient agroecological framework is one of the most pressing needs faced by our global community. Understanding the frequency of adoption and relationships between thethe use of multiple conservation practices can beis important in the to development of research, education, and policy to accelerate their more widespread integration of multiple practices into a farming systems by helping farmers to understand the benefits from adopting complementary practices. . The aim of this study was to conduct a preliminary investigation of the trends regarding the multiple practice adoption of conservation farming practices by conventional and organic farmers already known to engageengaging with sustainable farming methods. For this, forty farmers were interviewed to describeregarding their use of conservation practices, as well as their motivations, barriers, and future plans for new implementationadoption and expansion of current practices. Farmers spontaneously identifiedResults showed that the main implemented practices identified spontaneously by farmers are cover crops and vegetation strips as the most frequently used conservation practices; however, upon more specific inquiry, we found that , but that in fact more than 50% of farmers us cover crops,used additional agroecological conservation practices including grass strips, locallocal crop varieties, intercropping, managed grazing, crop rotations, and no-till, with . And that many farmers usinge multiple practices. Overall, we found no significant correlation of organic certification with the number of conservation practices implemented by farmers. The major motivations towards the adoption of practices included improved soil quality and profitability. Main identified barriers included financial means and risk, lack of knowledge, and access to resources. Farmers showed interest in further implementationadoption of for future additional conservation practices,s including implementation with expanding theexpanded use of cover crops, planting more treestree , andplantings, and expanded or new implementation of no-till practices. Further The results of the interviews highlighted the importance of an improved understanding to design complementarity between more frequent and lesser used practices as a way derive additional agroecological